Overcoming the barriers to promoting online interprofessional education - Forman, Dawn; Jones, M. (IGI Global, 2010)
It is not always transparent how e-learning can facilitate the interaction necessary for individuals to learn with, from and about each other as advocated by CAIPE (2002). This chapter emphasises the critical importance of facilitators acquiring new techniques to enable learners to make optimum use of the opportunities provided by Electronic Interprofessional Education (EIPE). To understand how barriers to online interprofessional education can be overcome, it is necessary to understand approaches to the development of positive e-learning environments. With this understanding, e-learning in supporting Interprofessional Education can be implemented more smoothly for both academic staff and students. © 2010, IGI Global.